2015
DOI: 10.1177/1933719114537717
|View full text |Cite
|
Sign up to set email alerts
|

Increased Progesterone Production in Cumulus—Oocyte Complexes of Female Mice Sired by Males With the Y-Chromosome Long Arm Deletion and its Potential Influence on Fertilization Efficiency

Abstract: It was revealed previously that B10.BR(Y del ) females sired by males with the Y-chromosome long arm deletion differ from genetically identical B10.BR females sired by males with the intact Y chromosome. This is interpreted as a result of different epigenetic information which females of both groups inherit from their fathers. In the following study, we show that cumulus-oocyte complexes ovulated by B10.BR(Y del ) females synthesize increased amounts of progesterone, which is important sperm stimulator. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Finally, given the documented imprinted effects of Yq deletion on the cumulus cell properties of daughters of B10.BR-Y del males [27], we tested whether there was an imprinted effect on the sex ratio skew by mating X GFP Y RIII qdel and X GFP Y RIII males (n = 7 males tested per genotype) to daughters of XY RIII qdel or XY RIII males and scoring the resulting offspring. In this experiment, the females were not superovulated and the embryos were dissected and scored for GFP in mid-gestation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, given the documented imprinted effects of Yq deletion on the cumulus cell properties of daughters of B10.BR-Y del males [27], we tested whether there was an imprinted effect on the sex ratio skew by mating X GFP Y RIII qdel and X GFP Y RIII males (n = 7 males tested per genotype) to daughters of XY RIII qdel or XY RIII males and scoring the resulting offspring. In this experiment, the females were not superovulated and the embryos were dissected and scored for GFP in mid-gestation.…”
Section: Resultsmentioning
confidence: 99%
“…They are fertile, but produce sperm of lower quality than their B10.BR counterparts. Numerous past studies revealed frequent morphological and ultrastructural abnormalities [Styrna et al 1991a;Styrna et al 1991b;Styrna et al 2002], deterioration of movement parameters [Grzmil et al 2007], difficulties in crossing uterotubal junction [Kotarska and Lenartowicz 2011], aberrant expression of surface receptors [Kotarska et al 2015], and lower fertilization efficiency of B10.BR-Y del spermatozoa [Xian et al 1992;Styrna et al 2002; Kotarska and Styrna 2012]. All these studies were focused, however, only on young adult individuals.…”
Section: Resultsmentioning
confidence: 99%
“…We used RT-qPCR to verify some differentially expressed genes identified via RNA-Seq, including MSTN, CTGF, NDUFA1, VCAN, SCD5, and STAR , which may be prognostic markers of oocyte quality. COCs are vital part of follicles that regulate follicle growth by secreting factors and communicating via gap junctions [ 19 ]. Oocytes regulate CCs proliferation and the sensitivity capacity of steroid hormones, while CCs regulate oocyte maturation, such as growth, meiosis, and ovulation [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%